(untitled) (Global Journal of Management and Business Research, 2023)
In common understanding traveling is the fact of leaving one place to another It is a change of residence housing A trip has in itself causes goals and the different qualifiers from the other Also can we distinguish the tourist study tour and escape The last cited is a phenomenon that suffered the majority of the characters in the works of Ivorian novelists Whether Johanne Sarah Alice Nafiassou Natou Sonanf Val rie Akissi Amoin and Malimouna all at a time where to another leave their original places for one elsewhere more or less uncertai At the difference of the Europeans who explain their presence on African soil by the needs and requirements of cooperation Africans consider Europe as the Eldorado Their presence on this continent is best to be research-based and of material goods that they must at all costs to acquire and return improve their lives at home Others are as political exiles The finding that emerges here is that the different displacements have not the same causes or the same goals Some travels have cause poverty or political persecution other causes of aid but all have lucrative purposes The reasons are often financial social or human